PEMANFAATAN LIMBAH JAGUNG MENJADI PUPUK ORGANIK UNTUK PENYUBURAN LAHAN PERTANIAN - Mulyono, Daru (BPPT)
The use of maize waste plant materials (stem, leaf, and husk cover) have high economic value to be processed become organic fertilizer for agricultural land fertilizer. Maize have several and quite high contents of macro and micro nutrients. This activity was hoped that the farmers can overcome the increasing price of inorganic fertilizer recently and furthermore farmers can reap higher income. Beside higher income the use of organic fertilizer can improve the nature and behaviourof land through improving of soil chemical, soil physical, and soil microorganism. Therefore, the appropriate technology for processing of maize become organic fertilizer is very important to be diffused or socialized to farmers.Keywords: fertilizer, maize waste